2022
DOI: 10.1016/j.jaci.2021.09.014
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 signaling in sensory neurons promotes dry skin itch

Abstract: Research in the Kim laboratory is supported by the Celgene Corporation, Doris Duke Charitable Foundation, LEO Pharma, and National Institute of Arthritis and Musculoskeletal and Skin Diseases (NIAMS) (K08AR065577, R01AR070116, R01AR077007, and R21AI167047) (to B.S.K.). A.M.T. and M.R.M. are supported by National Institute of Allergy and Infectious Diseases (NIAID) (T32AI007163). A.M.T. and L.K.O. are supported by National Heart, Lung, and Blood Institute (NHLBI) (T32HL007317). A.M.T. is supported by NIAID (F30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 35 publications
1
34
0
2
Order By: Relevance
“…Moreover, IL-33/ST2 signaling was found to mediate chronic itch in a mouse model of contact hypersensitivity through the astrocytic JAK2/STAT3 cascade [140]. IL-33 was also shown to evoke calcium responses in neurons, with enhanced CQ evoking calcium responses [138]. Taken together, these findings suggested that IL-33 also functions as a modulator to enhance itch.…”
Section: Ltcmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, IL-33/ST2 signaling was found to mediate chronic itch in a mouse model of contact hypersensitivity through the astrocytic JAK2/STAT3 cascade [140]. IL-33 was also shown to evoke calcium responses in neurons, with enhanced CQ evoking calcium responses [138]. Taken together, these findings suggested that IL-33 also functions as a modulator to enhance itch.…”
Section: Ltcmentioning
confidence: 90%
“…IL-33 was also recently shown to be constitutively expressed in other cells, including DCs, macrophages, mast cells, fibroblasts, smooth muscle cells, platelets and megakaryocytes [135,136]. ST2 expressing cells include basophils, mast cells, eosinophils, macrophages, DCs, NK cells, NKT cells, Th2 cells, cytotoxic T cells, Tregs, B cells, ILCs, microglia, astrocytes, neurons, epithelial cells, endothelial cells, and fibroblasts [135,137,138]. Treatment of AD model mice with anti-IL-33 antibody improved AD-like symptoms, including scratching behavior [139].…”
Section: Ltcmentioning
confidence: 99%
“…Neuronal itch can be induced by the receptors for TSLP, IL-4, IL-13, IL-31, and IL-33 expressed on sensory neurons ( 40 41 ). Allergen-induced crosslinking of IgE activates granulocytes, including mast cells and basophils, via Fcε receptor I (FcεRI).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Excessive release of IL-33 from keratinocytes irradiated with poison ivy-derived allergen urushiol enhances the calcium influx in dermal peripheral dorsal root ganglia neurons through its receptor, ST2, to evoke itch and inflammatory responses ( 172 ). Neuronal ST2 signaling is a critical regulator of the development of the dry skin itch, but not an itch associated with atopic dermatitis ( 173 ). On the other hand, pathogen-derived lipopeptides, such as fibroblast-stimulating lipopeptide-1, can activate TLR2 in dorsal root ganglia, which, in turn, leads to infiltration of macrophages and release of IL-33 from keratinocytes.…”
Section: Il-33mentioning
confidence: 99%